Function Approximation Using Haar Wavelets - Jüri Majak and Martin Eerme and Anti Haavajõe and Karunanidhi Ramachandran and Dieter Scholz and Anti Lepik (AIP conference proceedings, 2020)
The generalized approach for function approximation using Haar wavelets is proposed. An approach proposed is based on higher order wavelet expansion and algorithms for determining integration constants. The theoretical study is validated by numerical analysis. The decrease of the absolute error and increase of the numerical rate of convergence with respect to mesh has been observed in comparison with approach available in literature.